Leverage leadership : a practical guide to building exceptional schools - Bambrick-Santoyo, Paul, 1972-; Peiser, Brett M., 1968- (San Francisco : Jossey-Bass, 2012)
'Examines seven principles at the core of effective leadershipPaul Bambrick-Santoyo (Managing Director of Uncommon Schools) shows leaders how they can raise their schools to greatness by following a core set of principles. These seven principles, or'levers,' allow for consistent, transformational, and replicable growth. With intentional focus on these areas, leaders will leverage much more learning from the same amount of time investment. Fundamentally, each of these seven levers answers the core questions of school leadership: What should an effective leader do, and how and when should they do it. Aimed at all levels of school leadership, the book is for any principal, superintendent, or educator who wants to be a transformational leader. The book's companion DVD includes 30 video clips of top-tier leaders in action. These videos bring great schools to you, and support a deeper understanding of both the components of success and how it looks as a whole. There are also many helpful rubrics, extensive professional development tools, calendars, and templates. Explores the core principles of effective leadership Author's charter school, North Star Academy in Newark, New Jersey, received the highest possible award given by the U.S. Department of Education; the National Blue Ribbon Includes an instructive DVD with 30 video clips to show how it looks in real life Bambrick-Santoyo has trained more than 1,800 school leaders nationwide in his work at Uncommon Schools and is a recognized expert on transforming schools to achieve extraordinary results'--
Book is accompanied by one computer optical discs entitle' Leverage leadership : a practical guide to building exceptional schools' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
Keywords: School management and organization; School improvement programs; School principals -- Professional relationships